Is Islam a religion of ease or hardship? an analysis of the Muslim scripture and patterns of Prophet Muhammad (Peace Be upon Him) - Ushama, Thameem (Canadian Center of Science and Education, 2015)
This paper analyses whether Islam is a religion of ease or hardship. It defines the Arabic terms used in the Scripture and Prophetic Traditions. It employs the method of content analysis of relevant verses of the Scripture and statements of Prophet Muhammad (peace be upon him) that refer to the feature of ease and removal of hardship in religion and its legal injunctions. It highlights scholars’ classification of hardship. It explores theoretical evidence for ease and removal of hardship in the Scripture and Patterns of the Prophet (peace be upon him). It also focuses on applied evidence by highlighting the methodology of conveying God’s Message and the methodology of applying the Divine injunctions in real life, including the Prophet’s engagement with ease and facilitation and his dispositions in interpreting the revealed texts along with his verdicts manifesting flexibility. This is followed by the stands of the Prophet’s Companions and the Successors in relation to ease and removal of hardship.